Developing an inventory to measure anger in mexican children/ desarrollo de un inventario para la medición de la ira en niños mexicanos/ desenvolvimento de um inventário para a mediação da ira em crianças mexicanas (2012)
Based on the state-trait model of anger (Spielberger, 1988, 1999), the aim was to develop a reliable and valid inventory to measure anger in Mexican children. Exploratory factor analyses on responses from 592 children (302 boys, 290 girls) (M=10.35 years old, SD=1.14) revealed four factors suggesting construct validity: 6-item state anger (e.g., "I am upset"), 5-item trait-temperament (e.g., "I get mad easily"), 7-item angerout (e.g., "I fight with whoever made me mad"), and 12-item anger control (e.g., "I try to relax"). Alpha reliabilities were .76, .76, .73, and .88, respectively. Anger control correlated negatively with other factors, whereas other factors correlated positively with each other. The inventory also had concurrent validity with an instrument that measured physical aggression.